Implementation of a novel MRI protocol for diagnosing femoral neck fractures in high energy femoral shaft fractures: One year results. Issue 8 (August 2021) - Rogers, Nathan B.; Achor, Timothy S.; Kumaravel, Manickam; Gary, Joshua L.; Munz, John W.; Choo, Andrew M.; Routt Jr, Milton L.; Warner, Stephen J.
Highlights: Rapid-sequence MRI reliably increases the rate of diagnosis of femoral neck fractures not identified on conventional Xray or CT imaging. Associated ipsilateral femoral neck fractures in patients with high energy femoral shaft fractures are more common than previously reported. Utilizing multi-disciplinary team efforts, MRI can reliably be performed in polytraumatized patients in an expedient manner. Of patients with a negative MRI, none have been found to have a missed or delayed femoral neck fracture. Abstract: Introduction: : Preliminary results using a novel rapid-sequence MRI to diagnose ipsilateral femoral neck fractures in patients sustaining high-energy femoral shaft fractures have been favorable compared to radiographic and CT imaging alone. To evaluate and optimize this new institutional imaging protocol further, we reviewed our results one year after implementation. Methods: : Rapid-sequence MRI was added to the imaging evaluation of patients with high-energy femoral shaft fractures without femoral neck fractures identified on radiographs or CT imaging. Data was retrospectively reviewed from a consecutive series of patients who met inclusion criteria. Results: : From September 2018 through September 2019, 114 patients sustained 121 high-energy femoral shaft fractures. The average patient age was 29.9 years, 73.7% (84/114) of patients were male, and 16.5% (20/121) were open fractures. Of patients indicated for a rapid-sequence MRI, 86% (92/107) underwent MR imaging. 5% (6/121) of patients had an ipsilateral femoral neck fracture identified on radiographs alone. Three additional femoral neck fractures were identified with CT imaging for an initial incidence of 7.4% (9/121). MRI identified 10 additional non-displaced femoral neck fractures, three complete and seven incomplete fractures, for an incidence of 15.7% (19/121). All identified femoral neck fractures were stabilized. Discussion/Conclusion: : The addition of rapid-sequence MRI of the pelvis in patients with high-energy femoral shaft fractures reliably increases the diagnosis of ipsilateral femoral neck fractures not identified with standard imaging. There were no cases of missed/delayed femoral neck fractures in patients with a negative MRI. This new imaging protocol effectively and safely improves the diagnosis of this injury pattern.